GCT-04. Pattern of Treatment Failures in Central Nervous System Non-Germinomatous Germ Cell Tumors (CNS-NGGCT): A Pooled Analysis of Clinical Trials. (3rd June 2022) - Fonseca, Adriana; Faure-Conter, Cecile; Murray, Matthew; Fangusaro, Jason; Bailey, Shivani; Goldman, Stewart; Khatua, Soumen; Frapaz, Didier; Calaminus, Gabriele; Dhall, Girish; Nicholson, James; Bouffet, Eric; et al.
Abstract: BACKGROUND: Central Nervous System- Non-Germinomatous Germ Cell Tumors (CNS-NGGCT) are rare but curable tumors. Due to their rarity, treatment failures remain a poorly characterized disease with unfavorable outcomes. In this study, we sought to characterize the treatment failures in a large cohort of prospectively treated patients. METHODS: European and North American clinical trials for patients with CNS-NGGCT (SIOP-GCT96, SFOP-TGM TC 90/92, COG-ACNS0122 and COG-ACNS1123) were pooled for analysis. Additionally, patients included and treated in the UK and France national registries under strict protocol-guidelines were included as an independent, non-overlapping cohort. RESULTS: A total of 118 patients experienced a treatment failure. Twenty-four patients had progressive disease during therapy and additional eleven patients were diagnosed with growing teratoma syndrome (GTS). Patients with GTS are significantly younger and present with local failures and negative tumor markers. Eighty-three individuals experienced disease relapses after treatment ended. Patients' metastatic relapses presented significantly earlier than local relapses and were associated with tumor marker elevation (OR: 4.39; p=0.026). In our analysis, focal or whole ventricular (WVI) radiation therapy was not associated with an increased risk of metastatic relapses. CONCLUSIONS: Herein, we present the largest pooled dataset of prospectively treated patients with relapsed CNS-NGGCT. Our study identified younger age and negative tumor markers to be characteristic of GTS. Additionally, we elucidated that metastatic relapses occur earlier than local relapses, are associated with elevated tumor markers, and are not associated with the field of radiation therapy. These findings are of utmost importance for the planning of future clinical trials and the implementation of surveillance strategies in these patients.